An Inquiry Blended SECI Model-Based Learning Support Approach for Promoting Perceptions and Learning Achievement of University Students - Krittawaya Thongkoo (2018)
© 2017 IEEE. Both inquiry-based learning approach and SECI (Socialization, Externalization, Combination, and Internalization) model of knowledge management are necessary elements for developing learning support environment to university students. Therefore, this study proposed an inquiry blended SECI model to scaffold university students through knowledge sharing, internalization, and inquiry-based learning processes. An online learning support system was developed basing on the proposed inquiry blended SECI model and implemented in a web-programming course. Ninety-one university students were recruited to participate in this study. The experimental results showed that the university students who learned with the proposed system had better perceptions toward the learning support system and better learning achievement than those who learned with the traditional learning support system.